UNDERSTANDÄ°NG SUSAN BORDO AND HER WORK; UNBEARABLE WEÄ°GHT :FEMÄ°NÄ°SM, WESTERN CULTURE, BODY - DEMÃ„Â°R, ÃƒÂ‡AÃ„ÂžLAR (Journal of Humanity, 2017)
Throughout history of thought, there have been many views about the women, their status in society, their struggle with patriarchy, and inequalityÂ applied to them in all areas. There are different ways of oppression on women, such as confinement to home, inequality in wages between both sexes.Â However, few scholars have written and declared their own views about how the patriarchal world and companies form women as they wish. Susan Bordo is one ofÂ the most outstanding and distinguished feminist writers in the world who focuses onÂ how patriarchal capitalist understanding works on womenâs body in terms of weight and weakness. According to Susan Bordo, male dominated capital world decides on women about what to wear and what to eat and women try to lose weight to be in the form men wish. State ofÂ starving all the time leads to an illness called anorexia. The writer bases her views on the thoughts of literary critic and thinker, Foucault. TheÂ objective of this article is to help the readers understand Susan Bordoâs views and analyse her impressive work; Unbearable Weight: Feminism, Western Culture andÂ the BodyÂ and make her known in academic world.